Load carrying capacity of inclined crossing screws in glulam-concrete composite beam with an interlayer. (1st August 2020) - Du, Hao; Hu, Xiamin; Sun, Zhixiang; Meng, Yanfei; Han, Guohui
Abstract: In many practical applications of timber-concrete composite (TCC) structures, especially in rehabilitation of timber buildings, the floorboard interlayer is utilized as formwork for pouring concrete slab. So far, few researches have been conducted to study the shear performance of inclined crossing screws in TCC beam with an interlayer. In this paper, seven groups of shear tests were conducted to study the shear performance of inclined crossing screws in glulam-concrete composite beam with an interlayer. The analyses focused on the effects of embedded length of screw into glulam, thickness of the concrete slab and screw diameter on the failure mechanism, the load-slip behavior and the load carrying capacity. Two typical failure mechanisms were observed: cone failure of the concrete layer around shear-compression screw and pull-out failure of shear-tension loaded screw. The test results demonstrated that with the increase of screw diameter and embedded length of screw into glulam, the load carrying capacity of the inclined crossing screws was enhanced. According to theoretical studies, in timber-concrete composite beams with interlayer, the calculation method for predicting load carrying capacity of inclined crossing screws was proposed, and significantly the predicted results agreed well with the experimental results.